STATE SUPPORT FOR REGIONAL DEVELOPMENT: Array - Sukhonos, M.; Dymchenko, O.; Belyavceva, Belyavceva; Gaydenko, S.; Svichko, S. (Municipal economy of cities. Series: «Economy science», 2019)
The article discusses the connection of the state policy of regional development with the tasks of local authorities in support of self-development of regions. It is determined that the world practice of economic development in recent decades has undergone a significant acceleration. However, the situation is such that the scientific support of these real processes in practice does not make it. The article defines a management function that is considered as a specific type of management activity, the relation of part to the whole. Other characteristics (properties) of managerial functions - procedural repetitive, technological, process. In the system of administrative management, the nature of functions is now radically changing. The region is considered not only as a standard large economic object of territorial placement and administrative subordination, but an object is a highly structured, in nature close to self-organized systems and living organisms, endowed with such qualities as nonlinearity, vulnerability, behavior, reflection, unpredictability. The problem of regional development management, its methodology, engineering and business practice are the components of a unified mechanism in which human needs and interests, production base and market conditions of life support create economic relations, an improved model of which is proposed. The logical - structural models of the activity of regional administrations organization to solve problems of regions, determination of specificity of regions as objects of controlled development are offered. Terminological explanations of the term "regulation, provision, support" are given. Characteristics of the Kharkiv region from the standpoint of their socio - economic potential are presented and changes are identified in the activity of the Kharkiv Region State Administration (KRSA) in the new conditions of the reform and development of local self - government. The tasks of scientific support and activation of processes of regional development are set.